UJI LAIK FUNGSI JALAN RUAS JALAN NASIONAL BATAS KOTA MANADO-KOTA TOMOHON STA 7+770-STA 26+966 - Lucia Ingrid Regina Lefrandt (Himpunan Pengembangan Jalan Indonesia (HPJI), 2022)
Abstract The condition of a road segment that meets the technical requirements and administrative requirements indicates that the road segment meets the road function worthiness criteria. This study aims to review the road safety aspect from the results of the road function worthiness test and is carried out using a qualitative method based on the procedures for implementing the road function worthiness test, in accordance with the Regulation of the Minister of Public Works Number 11/PRT/M/2010. The data obtained from the test results and field surveys are processed to obtain roadworthiness categories, with reference to the 6 technical components of the road, namely road geometry, road pavement structures, complementary buildings, road sections, traffic engineering management, and road equipment. The Manado-Tomohon City Boundary National Road was chosen as the object observed in this study. The purpose of this study was to analyze the level of road function worthiness and the repairs needed to make the road feasible based on the criteria contained in the Road Functional Worthiness Test. This study shows that the observed road section, namely the Manado City-Tomohon City Boundary road section is included in the conditional function-worthy category, which requires some technical improvements. Technical improvements that must be fulfilled include routine maintenance and procurement of road components that do not yet exist, so that the Manado City-Tomohon City Boundary road can actually become a functional road. Keywords: road; road technical standards; road geometry; road pavement; traffic Abstrak Kondisi suatu ruas jalan yang memenuhi persyaratan teknis dan persyaratan administratif menunjukkan bahwa ruas jalan tersebut memenuhi kriteria laik fungsi jalan. Studi ini bertujuan untuk meninjau aspek keselamatan jalan dari hasil uji laik fungsi jalan dan dilaksanakan dengan menggunakan metode kualitatif berdasarkan tata cara pelaksanaan uji laik fungsi jalan, sesuai Peraturan Menteri Pekerjaan Umum Nomor 11/PRT/M/2010. Data yang diperoleh dari hasil uji dan survei lapangan diolah untuk mendapatkan kategori kelaikan jalan, dengan mengacu pada 6 komponen teknis jalan, yaitu geometrik jalan, struktur perkerasan jalan, bangunan pelengkap, bagian jalan, manajemen rekasaya lalu lintas, dan perlengkapan jalan. Ruas Jalan Nasional Batas Kota Manado-Kota Tomohon dipilih sebagai obyek yang dikaji pada penelitian ini. Tujuan penelitian ini adalah untuk menganalisis tingkat kelaikan fungsi jalan serta perbaikan yang diperlukan agar jalan menjadi laik berdasarkan kriteria yang terdapat pada Uji Laik Fungsi Jalan. Studi ini menunjukkan bahwa ruas jalan yang diamati, yaitu ruas jalan Batas Kota Manado-Kota Tomohon termasuk dalam kategori laik fungsi bersyarat, yang memerlukan beberapa perbaikan teknis. Perbaikan teknis yang harus dipenuhi meliputi pemeliharaan rutin dan pengadaan komponen jalan yang belum ada, agar ruas jalan Batas Kota Manado-Kota Tomohon benar-benar dapat menjadi jalan yang laik fungsi. Kata-kata kunci: jalan; standar teknis jalan; geometrik jalan; perkerasan jalan; lalu lintas